THE INTEREST OF CIVIL ENGINEERING DEPARTMENT STUDENTS AT PADANG STATE UNIVERSITY IN FOLLOWING STUDENT CREATIVITY PROGRAM ACTIVITIES (PKM) - 444-450 , Alitra (Universitas Negeri Padang, 2014)
Abstract This study was conducted to reveal the cause of low interest in following PKM activities of Civil Engineering Department Students, at Engineering Faculty of Padang State University (UNP). This case is caused by the fact that the Students’ interest is relatively low in following PKM activities in 2013. This study was conducted on students of Building Engineering Study Program of Civil Engineering Department at Engineering Faculty of UNP year 2010 and 2011. Total population in this study is 167. The numbers of samples for this study are 118; Students of year 2010 are 59 Students and the year 2011 are 59 students. Technique of data collection is using the Likert scale questionnaire. The results showed that the low of students’ interest in attending PKM activity is caused, among others: in the cognition indicator are the lack of Students’ knowledge in PKM proposals development and the lack of information obtained by the students, in the emotion indicator are less happy feelings in following PKM activities, as well as the lack of willingness of Students to follow PKM activities, and lack of students’ attention about PKM activities (in wish indicator). Keywords : Interest, Student Creativity Program (PKM).